PEMIKIRAN TRANSENDENSI DAN IMANENSI THOMAS AQUINAS DAN IMPLIKASINYA BAGI TEOLOGI PERIBADATAN PENTAKOSTA - Heru Cahyono (Diegesis : Jurnal Teologi, 2023)
The thought that God is far away is a problem for Pentecostals. At the same time, God is called the Father, who is close to greeting His people. This research provides specific answers to Thomas Aquinas' thoughts combined with Pentecostalism regarding the worship that God is present as transcendent and immanent. The research method used is descriptive qualitative with a constructive theological approach. The research results show that Pentecostals must first understand transcendence and immanence as a form of God's holy presence. In the worship of Pentecostals, the immanent God becomes proof that God is near when worshiping Him in spirit and truth, and God is transcendent and immanent that His existence is not only sought for proof but experienced.